Corporate investment and the exchange rate: The financial channel - Ryan Banerjee; Boris Hofmann; Aaron N. Mehrotra (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
Using firm-level data for 18 major global economies, we find that the exchange rate affects corpo-rate investment through a financial channel: exchange rate depreciation dampens corporate invest-ment through firm leverage and FX debt. These findings are consistent with the predictions of a stylised model of credit risk in which exchange rates can affect investment through FX debt or borrowing in local currency from foreign lenders. Empirically, the channel is more pronounced in emerging market economies (EMEs), reflecting their greater dependence on foreign funding and their less developed financial systems. Moreover, we find that exchange rate depreciation induces highly leveraged firms to increase their cash holdings, supporting from a different angle the notion of a financial channel of the exchange rate. Overall, these findings suggest that the large depreciation of EME currencies since 2011 was probably a significant amplifying factor in the recent investment slowdown in these economies.
URN:NBN:fi:bof-202003032009
Keywords: E22; F31; F41; O16; 330; corporate investment; emerging markets; exchange rates; financial channel; financial constraints